5(x+2)=9(x-26)

Simple and best practice solution for 5(x+2)=9(x-26) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+2)=9(x-26) equation:


Simplifying
5(x + 2) = 9(x + -26)

Reorder the terms:
5(2 + x) = 9(x + -26)
(2 * 5 + x * 5) = 9(x + -26)
(10 + 5x) = 9(x + -26)

Reorder the terms:
10 + 5x = 9(-26 + x)
10 + 5x = (-26 * 9 + x * 9)
10 + 5x = (-234 + 9x)

Solving
10 + 5x = -234 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
10 + 5x + -9x = -234 + 9x + -9x

Combine like terms: 5x + -9x = -4x
10 + -4x = -234 + 9x + -9x

Combine like terms: 9x + -9x = 0
10 + -4x = -234 + 0
10 + -4x = -234

Add '-10' to each side of the equation.
10 + -10 + -4x = -234 + -10

Combine like terms: 10 + -10 = 0
0 + -4x = -234 + -10
-4x = -234 + -10

Combine like terms: -234 + -10 = -244
-4x = -244

Divide each side by '-4'.
x = 61

Simplifying
x = 61

See similar equations:

| a^2+a=1 | | K-6.4=2.9 | | 448=-8(-10x+4) | | 4x+3(-5x-3)=-64 | | 7(5y-1)=28y | | 20=2+8k+k | | -3+5x-7=20 | | 90=(4x+3) | | 12+2z=5z+27 | | 5x-125=55 | | I-38=46 | | y=625+144 | | 36(x-2)= | | 85-x=10 | | 23-(7t-7)=45t-4 | | 5(2x-1)+2=7(x+3) | | J-647=353 | | -3x+6-2x=7x+8 | | -36+s=31 | | -396=-9(8x-12) | | 6(2x-4)=3(4x-22) | | 4a+3=-9 | | p^2-10p-15=0 | | 3t-18=4t-16 | | 6x-2=70 | | -498=6(9x+16) | | 20=-3x+7(-2x+25) | | -7(x+8)-44=3-61 | | 8x^3-336x^2+2760x+1608= | | 2(7-3x)+1=2x-1 | | (3x+4)(x-3)=10 | | 8+-176=-72 |

Equations solver categories